2009
DOI: 10.1007/s00520-009-0653-z
|View full text |Cite
|
Sign up to set email alerts
|

Determining the minimal clinically important difference criteria for the Multidimensional Fatigue Inventory in a radiotherapy population

Abstract: MCIDs validated in this study allow better interpretation of changes in MFI sub-scale scores and allow effect size calculations for determining sample size in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 25 publications
6
79
1
1
Order By: Relevance
“…An earlier study by this research team which examined fatigue with identical assessments and time-points in the same radiotherapy population (n=220) [22] found that fatigue increased significantly from baseline to end of treatment and then decreased significantly by 6-week follow-up echoing findings of similar research [3,36]. This discrepancy may be explained by potential compensatory rivalry between groups aware of the aim of the study or by sample bias.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…An earlier study by this research team which examined fatigue with identical assessments and time-points in the same radiotherapy population (n=220) [22] found that fatigue increased significantly from baseline to end of treatment and then decreased significantly by 6-week follow-up echoing findings of similar research [3,36]. This discrepancy may be explained by potential compensatory rivalry between groups aware of the aim of the study or by sample bias.…”
Section: Discussionmentioning
confidence: 67%
“…Each fatigue subscale has a potential score range from 4 to 20, where higher scores indicate more fatigue. The MFI subscales have previously been reported to have good internal consistency (average Cronbach's Alpha=0.81) [22] and overall has been demonstrated to be a valid instrument for use amongst people with cancer [26].…”
Section: Primary Outcome Measurementioning
confidence: 98%
See 1 more Smart Citation
“…In our trial, we observed significant improvements at discharge and at the end of the exercise intervention. Regarding the minimal clinically important differences in cancer-related fatigue scores reported for the different MFI subscales in cancer patients by Purcell et al, 39 our fatigue findings concerning "general fatigue" and "physical fatigue" can be regarded as clinically important and relevant. Previous studies on exercise and cancer-related fatigue have shown benefits in some, although not all, settings.…”
Section: Discussionmentioning
confidence: 93%
“…The MFI measures general, physical, and mental fatigue as well as reduced activity and motivation. A clinically meaningful difference in MFI scores is 10 points based on studies of cancer patients (Purcell et al, 2010). …”
Section: Methodsmentioning
confidence: 99%